2021
DOI: 10.4028/www.scientific.net/ssp.314.119
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Solutions of Replacement Metal Gate Patterning to Enable Gate-all-Around Device Scaling

Abstract: This paper addresses challenges and solutions of replacement metal gate of gate-all-around nanosheet devices. The unit process and integration solutions for the metal gate patterning as well as interface dipole patterning to offer multiple threshold voltage have been developed. The challenges of long channel device integration are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In the high-k metal gate (HKMG) of logic and memory periphery transistors, rare earth and some alkaline earth metals or their oxides, e.g. lanthanum oxide (La2O3) and magnesium oxide (MgO) have been proposed as a zero-thickness work function (WF) shifter [1][2][3][4][5]. However, the wet processing of such new materials is quite challenging because they easily dissolve in water, for example for La2O3 it was shown that a good control of the pH plays a key role to control its dissolution [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the high-k metal gate (HKMG) of logic and memory periphery transistors, rare earth and some alkaline earth metals or their oxides, e.g. lanthanum oxide (La2O3) and magnesium oxide (MgO) have been proposed as a zero-thickness work function (WF) shifter [1][2][3][4][5]. However, the wet processing of such new materials is quite challenging because they easily dissolve in water, for example for La2O3 it was shown that a good control of the pH plays a key role to control its dissolution [6].…”
Section: Introductionmentioning
confidence: 99%